Bank Loan Application Success of Innovative and Non-Innovative SMEs - van der Zwan, Peter (Senate Hall, 2016)
The investigation of the determinants of access to finance is relevant because restricted loan accessibility could hinder firm growth. This paper focuses on small- and medium-sized enterprises (SMEs) and whether their requested loan is granted by the bank. Financial data for SMEs in 29 European countries are used (four waves of the Survey on the Access to Finance of Enterprises during 2009-2014) to test the relationship between innovative behavior and loan application success. The contribution of the present study is that a distinction is made between product, process, and organizational innovation. Also, cross-national evidence on the link between innovation and loan turndown is provided while existing studies usually focus on a single country. The results indicate that SMEs that adopt innovations are less likely to receive the requested loan than SMEs that do not adopt innovations, and this holds for all three types of innovation. Additional analyses reveal the robustness of the results across various firm age and firm size categories, and the majority of countries. Keywords: credit constraints, SMEs, process innovation, product innovation, organizational innovation
Keywords: credit constraints|SMEs|process innovation|product innovation|organizational innovation